Shear and flexural bending strength of masonry wall Retrofitted using pp-band mesh - Sathiparan, N.; Meguro, K. (My University, 2013)
One of the main causes of casualties in major earthquakes around the world is the collapse of low earthquake resistant masonry structures. Retrofitting of these types of structures is the key issue for earthquake disaster mitigation in developing countries, because it is the only way to reduce significantly casualties in future earthquakes. This paper presents an innovative retrofitting method for masonry houses, which consists of polypropylene bands (PP-band) arranged in a mesh fashion. The PP-band technology aims to prevent or, at least, put off wall collapse by providing both sides with the mesh made of a cheap packthread and keeping the integrity of the walls. In order to verify the suitability of the proposed method, a series of masonry wallettes, with and without retrofitting, was tested under in-plane and out-of-plane loads. Although the retrofitted wall peak strength was almost the same as that of the bare wall, its postpeak strength was larger and sustained for lateral drifts. In order to investigate the proposed retrofitting features for different material properties and mesh configurations, tests on a number of masonry wallettes were performed.
Keywords: unreinforced masonry; PP-band